Mechanism of GLP-1 Receptor Agonists-Mediated Attenuation of Palmitic Acid-Induced Lipotoxicity in L6 Myoblasts. (28th December 2022) - Kong, Mo-wei; Gao, Yu; Xie, Yu-yu; Xing, En-hong; Sun, Li-xin; Ma, Hui-juan; Xing, Han-ying
Abstract : Object . L6 cells were cultured to explore the possible mechanism underlying the improvement of insulin resistance by Liraglutide (LR). Methods . Cells were divided into 5 groups—control, high-fat, 10 nmol/L LR + 0.6  mmol/L palmitic acid (PA) (10LR), 100 nmol/L LR + 0.6  mmol/L PA (100LR), and 1000 nmol/L LR + 0.6  mmol/L PA (1000LR). CCK-8 method to detect cell viability, GPO-PAP enzymatic method to detect intracellular triglyceride content, and reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) and western blotting methods to detect fatty acid translocase CD36 (FAT/CD36) and fatty acid binding protein 4 (FABP4) in L6 cells, glucose-regulated protein 78 (GRP78), glucose transporter 4 (GLUT4) expression at the mRNA and protein levels, respectively, were performed. Results . We found that after PA intervention for 24 h, the cell viability decreased significantly; the cell viability of the LR group was higher than that of the high-fat group (P < 0.01 ). After PA intervention, compared with those in the high-fat group, GRP-78, FAT/CD36, FABP4 mRNA ((4.36 ± 0.32 vs. 8.15 ± 0.35 ); (1.00 ± 0.04 vs. 2.46 ± 0.08 ); (2.88 ± 0.55 vs. 8.29 ± 0.52 ), P < 0.01 ) and protein ((3338.13 ± 333.15 vs. 4963.98 ± 277.29 ); (1978.85 ± 124.24 vs. 2676.07 ± 100.64 ); (3372.00 ± 219.84 vs. 6083.20 ± 284.70 ), both P < 0.01 ) expression decreased in the LR group. The expression levels of GLUT4 mRNA ((0.75 ± 0.04 vs. 0.34 ± 0.03 ), P < 0.01 ) and protein ((3443.71 ± 191.89 vs. 2137.79 ± 118.75 ), P < 0.01 ) increased. Conclusion . Therefore, we conclude that LR can reverse PA-induced cell inactivation and lipid deposition, which may be related to the change in GRP-78, FAT/CD36, FABP4, GLUT4, and other factors.